Community's perception of elderly abuse - Jesiendra, Jango (Universiti Malaysia Sarawak, (UNIMAS), 2013)
This qualitative study is on community's perception of elderly abuse. The samples of the study were among the community in Kuching, Sarawak and Tambunan, Sabah. This study purpose is to explore the perceptions of community on elderly abuse, identifying how the community perceives about risk factors and impacts of abuse to the elderly. Data was collected within 20 participants by face-to-face and in-depth interview and reached the saturation level. The data was analyzed manually. Interviews were audio-taped, transcribed and coded line by line and grouped together based on the related categories. The themes then emerged through the process of categorizing and re-categorizing. The themes are, participants'" feelings toward this issue are sad, pity and angry. Elderly abuse is an action of mistreatment and harm, emotional abuse is the most awful form of abuse, and it is the community's responsibility to stop the elderly abuse. Meanwhile for the risk factors, the themes divided into two that are abuser's characteristics and elderly'S characteristics. The themes on impacts of elderly abuse are depression, health status affected, neglected and isolated. It is hopyd that through this study it will add to further knowledge and increase the ,; community's awareness toward the elderly abuse arid [astly, the health care personnel in the future should give more focus to this issue a d having an actions toward the well-being of the elderly.